Identification and characterization of a 2,2-dichloropropionic acid (2,2-DCP) degrading alkalotorelant bacterium strain BHS1 isolated from Blue Lake, Turkey - Batool Hazim Abdul Wahhab; Nurul Fatin Syamimi Khairul Anuar; Roswanira Abdul Wahab; Marwan S.M. Al Nimer; Nurul HIdayah Samsulrizal; Azzmer Azzar Abdul Hamid; Mohamed Faraj Edbeib; Yilmaz Kaya; Fahrul Huyop (Journal of Tropical Life Science, 2020)
An acid, 2,2-dichloropropionic acid (2,2-DCP) is an active ingredient in herbicide (DalaponÂ®). Using 2,2-DCP as a model substrate, an alkalotolerant bacterium was successfully isolated from the Blue Lake, Turkey. This bacterium is a potential bioremediation agent of recalcitrant xenobiotic halogenated compounds. This study aimed to prove the efficacy of the alkalotolerance Bacillus megaterium BHS1 in degrading 2,2-DCP as the sole source of carbon. Biolog GEN III system and 16S rRNA analysis were used for the identification of the bacterium. It was discovered that the strain BHS1 is Bacillus megaterium, and the bacterium that was observed to thrive in alkaline conditions (pH 7.0âˆ’14.0), supplemented with varying concentrations of 2,2-DCP (from 20 to 60 mM). Growth of strain BHS1 was exceptional in 40 mM of 2,2-DCP at pH 9, corresponding to a cell doubling time of 17.7 hour, whereas was fully inhibited at 50 mM 2,2-DCP. Since halogenated pollutants can make their way into highly alkaline environments, therefore, identifying threshold levels of strain BHS1 with respect to alkaline-tolerance and maximum level of 2,2-DCP may prove pertinent. This is to ensure that an optimal environment is created for the bacteria to degrade 2,2-DCP-contaminated water. In addition, this is the first study exploring a Bacillus species isolated from an alkaline environment adept in utilizing 2,2-DCP as a sole source of carbon. Hence, the ability of this strain to degrade other types of haloalkanoic acids constitutes a worthy future study.